Molecular Characterization and TRAP Analysis of Gene in Dendranthema morifolium - Luo, Y; Li, Q; Wang, X; Yang, F; Nong, S; Li, Q; Zhu, D (Cellular and Molecular Biology, 2015)
The molecular maker system - TRAP was applied to develop a novel and more accurate method to identify the variety and establish the evolutionary relationship of different categories of Dendranthema morifolium. A software - GENESIS 2.4 was used to conduct the cluster analysis and genetic dendrogram establishment. The results showed that 202 different fragments were amplified with 6 pair primers using the TRAP marker system. The polymorphic fragments number is 45, which takes up to 22.3%. The cluster analysis showed that 4 materials used in this study can be classified into 2 main groups and 3 subgroups. The genetic identity is 0.0767 and the average genetic distance is 0.9236 among the four materials. A new tool using the TRAP marker system is more accurate and can be used to identify different categories of Dendranthema morifolium at molecular level.